2020
DOI: 10.1021/acs.nanolett.0c02115
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tunable SnS-TaS2 Nanoscale Superlattices

Abstract: Nanoscale superlattices represent a compelling platform for designed materials as the specific identity and spatial arrangement of constituent layers can lead to tunable properties. A number of kinetically stabilized, nonepitaxial superlattices with almost limitless structural tunability have been reported in telluride and selenide chemistries but have not yet been extended to sulfides. Here, we present SnS-TaS 2 nanoscale superlattices with tunable layer architecture. Layered amorphous precursors are prepared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Nucleation occurs at multiple sites within the precursors because any amorphous region formed during deposition onto the nominally room temperature substrates is supersaturated with respect to the crystalline constituents. Several recent reports discuss methods to control nucleation rates/sites, which could be used to reduce domain boundary and layer step defects. ,, Local variations in composition will always occur; therefore, controlling layer step defects would require controlling processing conditions and diffusion rates. , Our results also suggest that it should be possible to control the type and density of defects in these heterostructures by controlling the precursor structure and processing conditions to influence properties. Defects are desirable in some cases, such as reduced lattice thermal conductivity, which can be improved by increasing dislocation densities and decreasing grain size .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Nucleation occurs at multiple sites within the precursors because any amorphous region formed during deposition onto the nominally room temperature substrates is supersaturated with respect to the crystalline constituents. Several recent reports discuss methods to control nucleation rates/sites, which could be used to reduce domain boundary and layer step defects. ,, Local variations in composition will always occur; therefore, controlling layer step defects would require controlling processing conditions and diffusion rates. , Our results also suggest that it should be possible to control the type and density of defects in these heterostructures by controlling the precursor structure and processing conditions to influence properties. Defects are desirable in some cases, such as reduced lattice thermal conductivity, which can be improved by increasing dislocation densities and decreasing grain size .…”
Section: Discussionmentioning
confidence: 70%
“…Several recent reports discuss methods to control nucleation rates/sites, which could be used to reduce domain boundary and layer step defects. 6,31,32 Local variations in composition will always occur; therefore, controlling layer step defects would require controlling processing conditions and diffusion rates. 18,33 Our results also suggest that it should be possible to control the type and density of defects in these heterostructures by controlling the precursor structure and processing conditions to influence properties.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This experimental workflow at NREL has been benchmarked against other laboratories. 14 , 15 Other publications demonstrate the range of materials chemistries (e.g., oxides, 16 nitrides, 17 chalcogenides, 18 Li-containing materials, 19 intermetallics) 20 and properties (e.g., optoelectronic, 21 electronic, 22 piezoelectric, 23 photoelectrochemical, 24 thermochemical) 25 to which these HTE methods have been applied.
Figure 2 Experimental and data workflows for high-throughput materials research The workflow starts with (A) experiment design, then material samples are (B) produced, (C) treated, (D) measured, and (E) stored in archives.
…”
Section: Resultsmentioning
confidence: 99%
“…This experimental workflow at NREL has been benchmarked against other laboratories. 14,15 Other publications demonstrate the range of materials chemistries (e.g., oxides, 16 nitrides, 17 chalcogenides, 18 Li-containing materials, 19 intermetallics) 20 and properties (e.g., optoelectronic, 21 electronic, 22 piezoelectric, 23 photoelectrochemical, 24 thermochemical) 25 to which these HTE methods have been applied.…”
Section: Descriptormentioning
confidence: 99%
“…However, although many known misfit compounds are in the sulfide space, the fabrication of kinetically controlled sulfide superlattices is still challenging due to the experimental challenges during sulfur deposition. Very recently, Roberts et al [116] demonstrated the preparation of nanoscale SnS-TaS 2 superlattices with independent sulfur source from designed amorphous precursors, which were deposited by using a radiofrequency (RF) co-sputtering technique. It is the first report of artificial sulfide misfit superlattices with kinetically controlled architectures (Figure 6B).…”
Section: Misfit Layered Materialsmentioning
confidence: 99%